2023
DOI: 10.1002/asmb.2749
|View full text |Cite
|
Sign up to set email alerts
|

A new Wiener process with bathtub‐shaped degradation rate in the presence of random effects

Abstract: This paper proposes a new time scaled Wiener process with random effects that has been specially designed to allow the description of non‐monotonic degradation phenomena with bathtub shaped degradation rate, here intended as derivative of the mean function. Two different parameterizations of the proposed Wiener process are suggested, and the main features of the process are illustrated and discussed. The maximum likelihood estimation of its parameters is addressed. A failure threshold model is adopted to formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is shown that regular copula is a bad choice in this context, even if authors regularly use such models. The impact of this wrong choice of dependence modelling is studied and illustrated on practical applications. The paper from Giorgio, Piscopo and Pulcini 2 proposes new Wiener processes incorporating random effects and that allows to consider bathtub shaped phenomena on the degradation. The corresponding remaining useful life distribution is derived in a failure threshold context and a maximum likelihood estimation method is developed.…”
mentioning
confidence: 99%
“…It is shown that regular copula is a bad choice in this context, even if authors regularly use such models. The impact of this wrong choice of dependence modelling is studied and illustrated on practical applications. The paper from Giorgio, Piscopo and Pulcini 2 proposes new Wiener processes incorporating random effects and that allows to consider bathtub shaped phenomena on the degradation. The corresponding remaining useful life distribution is derived in a failure threshold context and a maximum likelihood estimation method is developed.…”
mentioning
confidence: 99%